Cyber Racism Toward Black Athletes: A Critical Race Analysis of TexAgs.com Online Brand Community. (December 2021) - Oshiro, Kristi F.; Weems, Anthony J.; Singer, John N.
While athletes in the 21st century have strategically leveraged technology and social media to disseminate their powerful truths (e.g., narratives) and to use as tools for organization, empowerment, and the disruption of hegemonic norms, sports fans have also found refuge on the internet and in cyberspace—namely, within online brand communities (OBCs). In this study, we draw from critical race theory (CRT) to interrogate cyber racism against Black male athletes in thehttp://TexAgs.com OBC. The primary purpose of this study was to conduct an exploratory collective case study of fan-generated discourse about Michael Bennett, Mike Evans, Myles Garrett, and Von Miller. Content analysis was used to examine and uncover the racially charged language directed toward these athletes. Three salient, interrelated themes were (1) good Aggie versus bad Aggie dichotomy, (2) dumb/misguided, and (3) thug. In line with the counter-narrative/storytelling tenet of CRT, we present Michael Bennett's (2018) personal narrative from his book to directly counter the racialized discourse about his peers and him on TexAgs. Based on the findings, we conclude with implications for sport communication and social justice in both the public sphere and cyberspaces.